Effects of vaccination status in the United States on willingness to undergo surgery during a pandemic: A prospective survey study. Issue 26 (9th June 2022) - Ruskin, Anna Clebone; Rice, Stephen; O'Connor, Michael; Ruskin, Keith J.
Abstract: Purpose of the Research: Modifiable and non-modifiable patient and hospital characteristics may affect willingness to undergo surgery during a pandemic. We hypothesized that vaccination of hospital staff and patients, type of surgery, and length of stay, would affect willingness to undergo a surgical procedure. 2006 adult participants in the United States were recruited electronically using Amazon's ® Mechanical Turk ® and answered a 26-item survey in English about hypothetical surgery, manipulating requirements for: staff vaccination, patient vaccination, surgical urgency, and time in hospital. They also answered questions about their opinions about vaccination, personal vaccination status, and demographics. Principle Results: Participants are more willing to undergo surgery if they have been vaccinated, if staff vaccinations are required, and if surgery is lifesaving and outpatient. Major Conclusions: Willingness to undergo surgery varies with hospital staff and patient vaccination. This may inform policies for vaccination, boosters, and resource allocation.